2022
DOI: 10.3390/fluids7080252
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Analysis on the Unsteady Flow of a Thermomagnetic Reactive Maxwell Nanofluid over a Stretching/Shrinking Sheet with Ohmic Dissipation and Brownian Motion

Abstract: The major objective of this current investigation is to examine the unsteady flow of a thermomagnetic reactive Maxwell nanofluid flow over a stretching/shrinking sheet with Ohmic dissipation and Brownian motion. Suitable similarity transformations were used to reduce the governing non-linear partial differential equations of momentum, energy and species conservation into a set of coupled ordinary differential equations. The reduced similarity ordinary differential equations were solved numerically using the Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The coupled system of Equations (20) and (21) , along with the boundary conditions specified in Equation (22) , is solved using the SQLM [48] , [49] , [50] , [51] , [52] . These equations are expressed using nonlinear ordinary differential systems.…”
Section: Numerical Solution Using Sqlmmentioning
confidence: 99%
See 1 more Smart Citation
“…The coupled system of Equations (20) and (21) , along with the boundary conditions specified in Equation (22) , is solved using the SQLM [48] , [49] , [50] , [51] , [52] . These equations are expressed using nonlinear ordinary differential systems.…”
Section: Numerical Solution Using Sqlmmentioning
confidence: 99%
“…Occasionally, this approach exhibited slow convergence or even failed to yield a solution. However, it was reported that the utilization of SQLM demonstrates a significantly higher convergence rate compared to existing numerical techniques, and its iterative steps are relatively straightforward to implement [50] , [51] , [52] . The distinctive feature of SQLM, contributing to its widespread acceptance as a numerical technique, was reported to be its ability to break down a complex set of nonlinear equations into smaller subsystems that are inherently more manageable.…”
Section: Numerical Solution Using Sqlmmentioning
confidence: 99%
“…Khan et al [6] explored the flow of a Maxwell nanofluid over an infinitely tall vertical plate with ramped and isothermal wall temperature and concentration. Shateyi and Hillary [7] conducted a numerical analysis on the unsteady flow of a thermomagnetic reactive Maxwell nanofluid over a stretching or shrinking sheet, considering ohmic dissipation and Brownian motion. In their research, Jawad et al [8] conducted an analytical study on the mixed convection flow of an MHD Maxwell nanofluid, considering variable thermal conductivity as well as Soret and Dufour effects.…”
Section: Introductionmentioning
confidence: 99%
“…[1] analyzed unsteady three dimensional bio-convective flow of Maxwell nanofluid over an exponentially stretching sheet with variable thermal conductivity and chemical reaction. [33] examined the unsteady flow of a thermomagnetic reactive Maxwell nanofluid flow over a stretching/shrinking sheet with Ohmic dissipation and Brownian motion.…”
Section: Introductionmentioning
confidence: 99%